Authenticity of Ficus Hispida as a Local Traditional Product in the Lembah Lenggong World Heritage Site - Abd Aziz, Siti Hajar; Zakaria, Zuraini; Rafiqi Mohammad, Ziyad (EDP Sciences, 2014)
Lembah Lenggong is a place well known amongst locals as an archaeological site; the valley has been attested as a World Heritage Site. There is an overwhelming variety of plant species that are uniquely used in their cultural and traditional cuisines including Ficus hispida (Senia). Ficus hispida is a well-known species restricted to the native people in Lembah Lenggong. It is recognized as one of the plants used specifically in the traditional cuisine of the locals, especially amongst the old folks. The plant leaves are a major part of a local traditional dish called ‘Masak Pindang’. The fruit of Ficus hispida is also edible, and consumed locally in candied form (halwa). In their traditional herbal remedies, Ficus hispida is used in treating wounds and as a medicine in post and pre natal care (maternal remedies). The desired outcome of this study is to emphasize and promote this specific species as one of the more unique products of Lembah Lenggong in a tourism aspect. The traditional knowledge and practices involving the use of Ficus hispida should be cherished and treasured by future generations to retain the authenticity of their local traditional and cultural products in the light of the awakening tourism industry.